Primary Malignant Melanoma of the Cervix: An Integrated Analysis of Case Reports and Series - Min, Aiping; Fu, Aizhen; Huang, Meiyuan; Wang, Hongjing; Chen, Huan (Frontiers in Oncology, 2022)
Melanoma, also known as malignant melanoma, is a type of malignant tumour that has its origins in melanocytes in the basal layer of the epidermis. Primary malignant melanomas of the female genital tract are rare. Primary malignant melanoma of cervix is an extremely rare disease that originates from cervical melanocytes and the second most common type of female melanoma in women aged 15 to 44 years worldwide. Although very rare, the prognosis for Primary malignant melanoma of cervix is quite poor. There is little consensus on the best treatment for it. The current treatments is based on FIGO staging with reference to NCCN guidelines. This study is in order to find a more suitable treatment modality for Primary malignant melanoma of cervix. Therefore, we first conducted an integrated analysis of case reports and series to assess the impact of various factors on the prognosis of such patients. In summary, this is the first pooled analysis including 149 cases of primary cervical melanoma. Patients who underwent radical hysterectomy-based surgery, those with non-lymph nodes metastatic and those who underwent lymphadenectomy had significantly higher survival rates. Based on the results of the analysis, the addition of other treatment options for patients undergoing radical hysterectomy-based surgery is subject to further study, but for those who had total hysterectomy-based surgery, the addition of other treatments to prolong median survival may be considered. Total hysterectomy-based surgery(insufficient scope of surgery) increases the risk of death in these patients, while lymphadenectomy reduces it, although there is no statistical difference, and lymphatic metastases also increase the risk of death.